CORRELATIONS IN QUANTUM PHYSICS - Dorner, R; Vedral, V (2013)
We provide a historical perspective of how the notion of correlations has evolved within quantum physics. We begin by reviewing Shannon's information theory and its first application in quantum physics, due to Everett, in explaining the information conveyed during a quantum measurement. This naturally leads us to Lindblad's information theoretic analysis of quantum measurements and his emphasis of the difference between the classical and quantum mutual information. After briefly summarizing the quantification of entanglement using these ideas, we arrive at the concept of quantum discord, which naturally captures the boundary between entanglement and classical correlations. Finally we discuss possible links between discord, which the generation of correlations in thermodynamic transformations of coupled harmonic oscillators. © 2013 World Scientific Publishing Company.